HIV Drug Efavirenz Inhibits CYP21A2 Activity with Possible Clinical Implications - Křenek Malíková, Jana; Zingg, Tanja; Fingerhut, Ralph; Sluka, Susanna; Grössl, Michael; Brixius-Anderko, Simone; Bernhardt, Rita; McDougall, Jane; Pandey, Amit V; Flück, Christa E (Hormone research in paediatrics, 2019)
BACKGROUND: The HIV drugs lopinavir and ritonavir have recently been reported to cause transient adrenal insufficiency in preterm newborns. We, therefore, considered HIV drugs as a cause of transiently elevated 17-hydroxyprogesterone (17OHP) levels in a neonatal screening test for congenital adrenal hyperplasia in a preterm girl exposed to zidovudine, efavirenz, tenofovir, and emtricitabine. OBJECTIVE: So far, HIV drugs have not been tested for their effect on steroidogenesis and the steroidogenic enzyme activity of CYP21A2 specifically in an in vitro system. METHODS: We tested the effect of efavirenz, tenofovir, emtricitabine, and zidovudine on steroidogenesis of human adrenal H295R cells. Cells were treated with the drugs at different concentrations including concentrations in therapeutic use. The effect on CYP21A2 activity was assessed by testing the conversion of radiolabeled 17OHP to 11-deoxycortisol. Cell viability was tested by an MTT assay. In addition, recombinant human CYP21A2 protein was used to assess direct drug effects on CYP21A2 activity. RESULTS: We observed significantly decreased CYP21A2 activity in both in vitro testing systems after treatment with efavirenz at therapeutic concentrations. Moreover, efavirenz affected cell viability. By contrast, the other test drugs did not affect steroidogenesis. Follow-up of our patient revealed elevated 17OHP and androgen levels during the first weeks of life, but values normalized spontaneously. Genetic testing for CYP21A2 mutations was negative. Thus, it remains unsettled whether the transient 17OHP elevation in this baby was due to a drug effect. CONCLUSION: The HIV drug efavirenz inhibits CYP21A2 activity in vitro through direct interaction with enzyme catalysis at therapeutic concentrations. This may have clinical implications for HIV treatment in children and adults. However, so far, clinical data are scarce, and further studies are needed to be able to draw clinical conclusions.
Keywords: steroid-21-hydroxylasa; Cell Line; Pregnancy Complications, Infectious; těhotenství; kongenitální adrenální hyperplazie; Premature Birth; Steroid 21-Hydroxylase; HIV infekce; Adrenal Hyperplasia, Congenital; Adult; benzoxaziny; inhibitory reverzní transkriptasy; infekční komplikace v těhotenství; Infant, Newborn; Benzoxazines; ženské pohlaví; novorozenec; předčasný porod; Humans; Pregnancy; zpožděný efekt prenatální expozice; Reverse Transcriptase Inhibitors; buněčné linie; dospělí; Female; HIV Infections; Prenatal Exposure Delayed Effects; lidé